Mannose Binding Lectin: A Potential Biomarker for Many Human Diseases - Sunil Singh, Senjam; Chi Fai Cheung, Randy; Ho Wong, Jack; Bun Ng, Tzi (Current Medicinal Chemistry, 2016)
The innate immune system plays a modulatory role in producing an inflammatory response during microbial infection and tissue regeneration. Mannose-binding lectin (MBL) is a predominant constituent of the innate immune system which initiates one of the complement activation, the lectin pathway. The activation of the complement system is also associated with many human diseases. We, therefore, try to summarize herewith the prognostic value of early detection of serum mannose-binding lectin (MBL) and measurement of its levels. The variant alleles and single nucleotide substitutions in MBL2 gene associated with MBL polymorphism are responsible for an increased risk of infection. Based on the currently available evidence, the role of MBL in humans is a double facet; sometimes its presence is associated with deterioration of the pathological condition while in other cases it is an important part of the body defense system. The importance of the determination of serum MBL as a diagnostic biomarker is duly addressed and then substitution of plasma-purified or recombinant MBL which can be a potential therapeutic for the treatment of human diseases is also highlighted. We have summarized in this article the pivotal roles of MBL in the early pathophysiology of various diseases and shown that MBL serves as a novel therapeutic target.
Keywords: Mannose binding lectins